The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1080/10584580390258165
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Integration of Embedded FeRAMs in the sub-180 nm Regime

Abstract: Ferroelectric memories (FeRAMs) are more and more using stack cells in 1T1C configuration. While none of these are already in real production, a great progress has been made when comparing these with strapped cells in 2T2C configuration. However the FeRAM community must be ready to face another challenging step in the evolution, i.e. the transition from planar to 3D capacitors. There's no consensus on the best approach to address this issue, which is probably a must at the 130 nm node. This paper reviews the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The use of CNTs as templates or as bottom electrodes is a potential strategy to realize 3D ferroelectric nanostructures. However, in the last few years only a few reports on the investigation of multiwalled carbon nanotubes (MWCNTs) covered with ferroelectrics for 3D capacitors and related applications have been published. ,, The use of MWCNTs for this application is limited by the requirement to process ferroelectrics at high temperatures (>600 °C) in oxidizing atmospheres, which results in an exothermic reaction. From our previous studies on the thermal stability of MWCNTs in different atmospheres, we have demonstrated that MWCNTs are stable up to 420 °C in air but in higher P­(O 2 ) they oxidize at ≥200 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The use of CNTs as templates or as bottom electrodes is a potential strategy to realize 3D ferroelectric nanostructures. However, in the last few years only a few reports on the investigation of multiwalled carbon nanotubes (MWCNTs) covered with ferroelectrics for 3D capacitors and related applications have been published. ,, The use of MWCNTs for this application is limited by the requirement to process ferroelectrics at high temperatures (>600 °C) in oxidizing atmospheres, which results in an exothermic reaction. From our previous studies on the thermal stability of MWCNTs in different atmospheres, we have demonstrated that MWCNTs are stable up to 420 °C in air but in higher P­(O 2 ) they oxidize at ≥200 °C.…”
Section: Introductionmentioning
confidence: 99%
“…One concern towards scaling is its charge-based operation and limited polarization signal, requiring the development of 3-dimensional (3-D) structures [1].…”
Section: Introductionmentioning
confidence: 99%
“…the ferroelectric capacitor, 'FeCAP') are required to attain a larger polarization signal per unit area of the memory cell. Thus, in the replacement of conventional planar capacitors, recent developments have been oriented toward integration of three-dimensional capacitors (Goux, Russo et al, 2005;Scott, 2005a,b;Scott et al, 2005;Nagel et al, 2004;Joshi, 2004;Narayan, 2003;Zambrano, 2003;Johnson et al, 2003). Lead zirconate titanate (PbZr 1Àx Ti x O 3 , PZT) is the most used ferroelectric material for planar capacitors and is also used for three-dimensional capacitor scaling (Nagai et al, 2006(Nagai et al, , 2005; Koo et al, 2005;Kim et al, 2005;Funakubo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, much attention is also focused on the integration of strontium bismuth tantalate (SrBi 2 Ta 2 O 9 , SBT) in threedimensional capacitors or in nanotubes (Morrison et al, 2003). Indeed, this material fulfills the requirements for highly reliable devices: high resistance to fatigue, long polarization retention, low leakage, negligible imprint and no degradation of electrical properties for ultra-thin films (Zambrano, 2003;Celinska et al, 2003;Scott, 2000;Paz de Araujo et al, 1995). Besides their good intrinsic electrical properties, high-quality polycrystalline SBT thin films are successfully elaborated by metal organic chemical vapour deposition (MOCVD) and fully integrated within a microelectronic architecture (Goux, Russo et al, 2005;Johnson et al, 2003;Narayan, 2003).…”
Section: Introductionmentioning
confidence: 99%